Effect of Mediterranean diet or mindfulness‐based stress reduction during pregnancy on placental volume and perfusion: A subanalysis of the IMPACT BCN randomized clinical trial - Ayako Nakaki; Eugenio Denaro; Maddalena Crimella; Roberta Castellani; Kilian Vellvé; Nora Izquierdo; Annachiara Basso; Cristina Paules; Rosa Casas; Leticia Benitez; Irene Casas; Marta Larroya; et al. (Acta Obstetricia et Gynecologica Scandinavica)
Abstract Introduction The IMPACT BCN trial—a parallel‐group randomized clinical trial where 1221 pregnant women at high risk for small‐for‐gestational age (SGA) newborns were randomly allocated at 19‐ to 23‐week gestation into three groups: Mediterranean diet, Mindfulness‐based Stress reduction or non‐intervention—has demonstrated a positive effect of Mediterranean diet and Stress reduction in the prevention of SGA. However, the mechanism of action of these interventions remains still unclear. The aim of this study is to investigate the effect of Mediterranean diet and Stress reduction on placental volume and perfusion. Material and Methods Participants in the Mediterranean diet group received monthly individual and group educational sessions, and free provision of extra‐virgin olive oil and walnuts. Women in the Stress reduction group underwent an 8‐week Stress reduction program adapted for pregnancy, consisting of weekly 2.5‐h and one full‐day sessions. Non‐intervention group was based on usual care. Placental volume and perfusion were assessed in a subgroup of randomly selected women (n = 165) using magnetic resonance (MR) at 36‐week gestation. Small placental volume was defined as MR estimated volume <10th centile. Perfusion was assessed by intravoxel incoherent motion. Results While mean MR placental volume was similar among the study groups, both interventions were associated with a lower prevalence of small placental volume (3.9% Mediterranean diet and 5% stress reduction vs. 17% non‐intervention; p = 0.03 and p = 0.04, respectively). Logistic regression showed that small placental volume was significantly associated with higher risk of SGA in both study groups (OR 7.48 [1.99–28.09] in Mediterranean diet and 20.44 [5.13–81.4] in Stress reduction). Mediation analysis showed that the effect of Mediterranean diet on SGA can be decomposed by a direct effect and an indirect effect (56.6%) mediated by a small placental volume. Similarly, the effect of Stress reduction on SGA is partially mediated (45.3%) by a small placental volume. Results on placental intravoxel incoherent motion perfusion fraction and diffusion coefficient were similar among the study groups. Conclusions Structured interventions during pregnancy based on Mediterranean diet or Stress reduction are associated with a lower proportion of small placentas, which is consistent with the previously observed beneficial effects of these interventions on fetal growth.